Francisco J. Ayala: Testing his Ideas on Biological Progress - Moya, Andrés; Latorre, Amparo (Razón y fe, 2024)
Francisco J. Ayala was one of the great scholars of progress in biological evolution. For Ayala, progress consists of a net directional change in some characteristic that improves the descendants in a given lineage relative to the ancestors. This is an axiological proposal, but not at all unscientific. The traits are objective properties that can be measured in individuals, populations, or species and, ultimately, the entire evolutionary tree. Here, we develop Ayala’s ideas about progress and propose that the trait where the trend can be contrasted is probably the complexity of genomes. We also consider the need to apply statistical tests to determine whether trends, if they exist, are passive products of evolution from the simplest to the most complex or whether, on the contrary, there is directionality or a process driven, among other things, by natural selection.
Keywords: progress; biological complexity; genome complexity; evolutionary trend; complexity metrics; symbiosis; regressive evolution